Pornification and the Mainstreaming of Sex - Paasonen Susanna (Oxford University Press, 2025)
The changing cultural role, visibility, and meaning of pornography, particularly its increased accessibility and the sociocultural reverberations that this is seen to cause, have been lively topics of public debate in most Western countries throughout the new millennium. Concerns are routinely yet passionately voiced, especially over the ubiquity of sexual representations flirting with the codes of pornography in different fields of popular media, as well as children’s exposure to hardcore materials that are seen to grow increasingly extreme and violent. At the same time, the production, distribution, and consumption have undergone notable transformations with the ubiquity of digital cameras and online platforms. Not only is pornography accessible on an unprecedented scale, but also it is available in more diverse shapes and forms than ever. All this has given rise to diverse journalistic and academic diagnoses on the pornification and sexualization of culture, which, despite their notable differences, aim to conceptualize transformations in the visibility of sexually explicit media content and its broader sociocultural resonances.
Oxford Research Encyclopedia of Criminology